A study on the factors influence job performance among employee at UCSI Hotel, Kuching / Nurezzati Azri and Ezatul Athirah Hassan - Azri, Nurezzati (2018)
In Malaysia, services sector is considered vital since it contributed around 54 percent to Gross Domestic Product (GDP) in the year 2012 (Department of Statistics Malaysia, 2012). By other words, more than half of GDP is contributed from services sector. By the way, tourism industry in Malaysia is constantly growing annually and it provides a considerable amount of national revenue to government. Hotel industry in Malaysia seems to be a promising business in this sector as the existence of tourism industry since tourists are considered as important customers. In addition, the profit of hotels is mainly come from tourists by providing accommodation and service to them.